Drug Court as an Intervention Point to Affect the Well-Being of Families of Parents with Substance Use Disorders. (15th April 2020) - Guastaferro, Kate; Guastaferro, Wendy P.; Brown, Jessica Rogers; Holleran, David; Whitaker, Daniel J.
Abstract: Background: A high proportion of justice-involved individuals have a substance use disorder and many of those individuals serve in a caregiving role to a child under 18. Given the negative impact of substance use and justice-involvement on the wellbeing of children, the criminal justice system may offer a unique intervention point with high public health impact. This study describes characteristics of adult drug court participants (DCP) that affect the wellbeing of their children and families and compares the DCP parenting and mental health characteristics to their child's other caregiver in order to understand how parenting differs within drug court families. Method: Data were collected from a sample of 100 DCP; 58 had a matched other caregiver. Drug court data regarding substance use and criminogenic risk/need were collected. Analyses differentiated the parenting behaviors and mental health needs of DCP from other caregivers. Results: The DCP were at moderate to high risk for recidivism and presented with multiple and significant criminogenic and psychosocial functioning needs. Risk for potential maltreatment and poor parenting behaviors were elevated, and significantly higher compared to other caregivers. DCP demonstrated clinically elevated mental health needs, and were significantly different across all indicators of mental health compared to other caregivers. Conclusions: Adult drug courts address the occurrence of substance use disorders but there are additional needs to be intervened upon. Adult drug courts may be a viable intervention point to address issues of parenting and mental health to improve the wellbeing of criminal justice-involved individuals, their children, and families.